Sex and outcomes of patients with microsatellite instability-high and BRAF V600E mutated metastatic colorectal cancer receiving immune checkpoint inhibitors - Michael Hoffmeister; Hermann Brenner; Chiara Cremolini; Sara Lonardi; Filippo Pietrantonio; Julien Taieb; David Tougeron; Robyn L Ward; Marco Vitellaro; Thierry André; Pierre Laurent-Puig; Jitendra Jonnagaddala; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICIs) are the gold standard therapy in patients with deficient mismatch repair (dMMR)/microsatellite instability-high (MSI-H) metastatic colorectal cancer (mCRC). A significant proportion of patients show resistance, making the identification of determinants of response crucial. Growing evidence supports the role of sex in determining susceptibility to anticancer therapies, but data is lacking for patients with MSI-H CRC.Methods In this real-world cohort comprising 624 patients with MSI-H mCRC receiving ICIs, we investigated the impact of sex on patients’ outcomes, overall and according to RAS-BRAF mutational status or type of treatment (anti-PD-(L)1 with or without anti-CTLA-4 agents). We then investigated these associations also in two independent cohorts of patients with early-stage or advanced MSI-H CRC unexposed to ICIs. Finally, we explored two public microarray and RNA-seq datasets from patients with non-metastatic or metastatic MSI-H CRC to gain translational insights on the association between sex, BRAF status and immune contextures/ICI efficacy.Results Although no differences were observed between females and males either overall or in the BRAF wild-type cohort, male sex was associated with inferior progression-free survival (PFS) and overall survival (OS) in the BRAF mutated cohort (in multivariable models, HR for PFS: 1.79, 95% CI: 1.13 to 2.83, p=0.014, and for OS: 2.33, 95% CI: 1.36 to 3.98, p=0.002). Males receiving anti-PD-(L)1 monotherapy had the worst outcomes, with a 3-year PFS and 3-year OS of 23.9% and 41.8%, respectively, while the addition of anti-CTLA-4 agents rescued such a worse outcome. We also observed that females experienced a higher frequency of any-grade immune-related adverse events. Conversely, sex was not prognostic in the independent cohorts of patients with MSI-H CRCs not treated with ICIs. Exploratory transcriptomic analyses suggest that tumors of males with BRAF mutated MSI-H metastatic CRC are characterized by an enrichment of androgen receptor signature and an immune-depleted microenvironment, with a reduction in memory B cells, activated natural killer cells, and activated myeloid dendritic cells.Conclusions Overall, our findings suggest a complex interplay between sex and BRAF mutational status that may modulate the activity of ICIs in patients with MSI-H mCRC and pave the way to novel tailored strategies.